Simplified finite element method analysis of ultra-high-performance fibre-reinforced concrete columns under blast loads. Issue 1 (January 2017) - Xu, Juechun; Wu, Chengqing; Li, Jun; Cui, Jintao
Ultra-high-performance fibre-reinforced concrete has exceptional mechanical properties including high compressive and tensile strength as well as high fracture energy. It has been proved to be much higher blast resistant than normal concrete. In this article, flexural behaviours of ultra-high-performance fibre-reinforced concrete columns were investigated through full-scale tests. Two 200 mm × 200 mm × 2500 mm columns with and without axial loading were investigated under three-point bending tests, and their load–displacement relationships were recorded and the moment curvatures were derived. The derived moment curvature relationships of ultra-high-performance fibre-reinforced concrete columns were then incorporated into a computationally efficient one-dimensional finite element model, which utilized Timoshenko beam theory, to determine flexural response of ultra-high-performance fibre-reinforced concrete columns under blast loading. After that, the one-dimensional finite element model was validated with the real blast testing data. The results show good correlation between the advanced finite element model and experimental results. The feasibility of utilizing the one-dimensional finite element model for simulating both high-strength reinforced concrete and ultra-high-performance fibre-reinforced concrete columns against blast loading conditions is confirmed.